2003
DOI: 10.1073/pnas.0931396100
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related changes in prostate DNA as men age and early identification of metastasis in primary prostate tumors

Abstract: Using statistical analyses of Fourier transform-IR spectra, we show that DNA of the histologically normal prostates of men 16 -80 years old undergoes structural changes in the bases and backbone with increasing age. Of the older men (ages 55-80), 42% exhibited a DNA phenotype mimicking that of primary prostate tumors from a comparable age group. This cancer-like phenotype, which was not found in the younger men (ages 16 -36), appears to arise from progressive age-related damage to DNA. The mean concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 32 publications
3
98
0
1
Order By: Relevance
“…Average adduct yield with 2 in 287 nt duplex DNA (2.5 pmol) as a function of 137 Cs dose. Circles, Na 2 IrCl 6 ; squares, K 3 Fe(CN) 6 .…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Average adduct yield with 2 in 287 nt duplex DNA (2.5 pmol) as a function of 137 Cs dose. Circles, Na 2 IrCl 6 ; squares, K 3 Fe(CN) 6 .…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Although both produced adducts with 2 in the presence of Na 2 IrBr 6 , only OxodG was trapped when K 3 Fe(CN) 6 was used as the oxidant (Figures 1 and 2). The selective biotinylation of DNA containing the lesions as a function of oxidant indicated that individual amounts of OxodG and Fapy•dG in randomly damaged DNA could be determined using 2 as part of a fluorescence assay (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These theories are consistent with experimental data from tissue cultures or animal models, but they are hard to reconcile with four critical facts: (a). previous studies have revealed that some healthy men between 19 and 29 years old demonstrated a spectrum of proliferative abnormalities in the prostate, including atypical hyperplasia, dysplasia, and incipient adenocarcinoma [11][12][13], (b) Recent studies have detected a DNA phenotype that is identical to the DNA structure of invasive prostate cancer in certain healthy men, and in normal prostate tissues adjacent to prostate cancer [14][15][16][17], (c) a majority of PIN express high le-vels of proteolytic enzymes, but only about 30% of untreated PIN progress to invasive lesions during patients' lifetime [18][19][20][21], and (d) results from worldwide human clinical trials with a wide variety of proteolytic enzyme specific inhibitors to treat or prevent tumor invasion have been very disappointing [22,23]. Together, these suggest that alternative mechanism(s) may exist for prostate tumor invasion.…”
Section: Focal Basal Cell Alterations and Disruptions In Tumor Capsulesmentioning
confidence: 99%
“…Early works focused on defining the tissue variability in terms of IR spectra (Chiriboga et al 1998a,b,c, Wood et al 2004. This led to a large number of studies with different tissues and cell lines with an objective to make the technique relevant to oncology (Fukuyama et al 1999, Diem et al 2000, Gao et al 1999, Yano et al 2000, Malins et al 2003. The potential application in other biomedical fields was expanded by studying the classification of microorganisms using the technique and using it for identifying pathogens , Choosmith et al 2001, Sandt et al 2003, Essendoubi et al 2005.…”
Section: Brief Historical Perspective Of Ftir Spectroscopy In Biomedimentioning
confidence: 99%